2016
DOI: 10.1021/jacs.6b09056
|View full text |Cite
|
Sign up to set email alerts
|

Xenon in Rigid Oxide Frameworks: Structure, Bonding and Explosive Properties of Layered Perovskite K4Xe3O12

Abstract: The tendency of high-valence xenon to form consolidated oxide structures is herein supported by the study of K4Xe3O12, the first example of a layered xenon perovskite. Xenon seems to be the only non-transition element which can adopt single-cation oxide perovskite frameworks. At the same time, peculiarities of electronic structure of xenon impose specific features on the bonding within a perovskite structure. Weak supramolecular interactions known as aerogen bonds are the linkers maintaining structural integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Remarkably, the authors showed that aerogen bonds are the NCIs that preserve the structural integrity of the perovskite. It is interesting to highlight that these compounds are explosive and the aerogen bonds have been proposed to be the trigger bonds responsible for the detonation [240,241].…”
Section: Aerogen Bondsmentioning
confidence: 99%
“…Remarkably, the authors showed that aerogen bonds are the NCIs that preserve the structural integrity of the perovskite. It is interesting to highlight that these compounds are explosive and the aerogen bonds have been proposed to be the trigger bonds responsible for the detonation [240,241].…”
Section: Aerogen Bondsmentioning
confidence: 99%
“…Xenon finds application in structural biology as a probe for solvent and gas channels in metalloenzymes, due to its high atomic number and hydrophobicity . It also shows binding affinity in supramolecular cages, oxide frameworks, MOFs, cryptophanes, and porous coordination‐complex salts; and has been widely used as an NMR probe for the determination of pore size in framework materials, due to the sensitivity of δ( 129 Xe) to its local environment…”
Section: Figurementioning
confidence: 99%
“…[15] Interestingly the 31 P{ 1 H} SSNMR spectrum now shows sharp signals at d À23. [21] It also shows binding affinity in supramolecular cages, [22] oxide frameworks, [23] MOFs, [24] cryptophanes, [25] and porous coordinationcomplex salts; [26] and has been widely used as an NMR probe for the determination of pore size in framework materials, [27] due to the sensitivity of d( 129 Xe) to its local environment. This transformation is reversible,a nd when [20] V Xe /V cavity = 0.43).…”
mentioning
confidence: 99%